Sine-based barnacle mating optimization for PD control of an inverted pendulum system - Muhammad Almaa Anwari, Roslan; Ahmad Nor Kasruddin, Nasir; Mohd Falfazli, Mat Jusof; Ahmad Azwan, Abd Razak; Mohd Ashraf, Ahmad (Springer Science and Business Media Deutschland GmbH, 2022)
This paper presents an improved optimization algorithm namely Sine-based Barnacle Mating Optimization (SbBMO) algorithm. The Barnacle Mating Optimization (BMO) applies a Barnacle mating concept in retaining the survival of their colony in its strategy. A Sine-based position update strategy is applied to all barnacles that are located at a distance away from their parent. This is to guide the barnacles towards the current best barnacle in the colony. It balances the mating strategy considering the dynamic step size of the sine-based strategy. The proposed SbBMO is tested on 10 dimensions of CEC2014 benchmark functions. The proposed algorithm is also applied to optimize Proportional-Derivative (PD) controller for controlling an inverted pendulum system. Result of the benchmark functions shows that the proposed SbBMO achieved a significant improvement on accuracy performance. For the inverted pendulum application, both algorithms have satisfactorily optimized the controller. However, the SbBMO-based PD achieved a more satisfactory control performance as compared to BMO-based PD.